Redefining Arabic Speaking Instruction through Visual-Based Mimicry Memorization Technique - Fina Rahmah; Muhammad Nu'man; Ely Mufidah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
This study aims to describe the application of the Mimicry Memorization (Mim-Mem) method with visual media pictorial PPT in learning Arabic language theme من يوميات الأسرة (family daily activities). in class VII MTsN 2 Sidoarjo. The research used the method of classroom action research (PTK) model Kemmis and McTaggart with a qualitative approach combined with simple quantitative analysis. The research subjects totaled 32 students. Learning is carried out through several stages, starting from the introduction of vocabulary with pictures, repetitive sentence imitation exercises, simple questions and answers, to short dialogs in pairs. Visual media in the form of PPT slides helped students understand the context, while the Mim-Mem method trained them to imitate, memorize, and apply vocabulary and sentence structures. This process is proven to increase students' activeness and courage to speak Arabic in front of the class. The results showed an increase in students' speaking skills in four aspects of assessment, namely pronunciation (3.63), vocabulary accuracy (3.72), fluency (3.84), and courage (3.94), with an overall average score of 3.78. This proves that the Mim-Mem method based on visual media is effective for improving students' speaking skills in Arabic language learning